(untitled) (Connessioni remote. Artivismo_Teatro_Tecnologia, 2021)
Artivism is first of all the dialogue between ethics, aesthetics and society. This topic is extremely relevant in a civilization which is invaded, overstimulated and deeply disoriented by an endless present. Concepts as art and culture themselves are nowadays undertaking a metamorphosis which is far beyond what Benjamin or Pasolini had prophesized. The 21st Century has exploded in the heart of western civilization, followed by the birth of new artistical, political and social ways of expression. This essay focuses on political theater today through the case of study of Rojava, a topic which has recently loomed in European performing arts. Supporting our work, together with the international secondary literature (Lehmann 2002, Monteverdi 2020, Valentini 2020 et al.), is the theater and research group Future II Konjunktiv (Berlin), author, among many workswhich are focus of this essay, of the book „HOCH DIE INTERNATIONALE SOLIDARITÄT!“.THEATER & THEORIE, TEXTE & BILD (Neofelis, Berlin 2021).